2018
DOI: 10.11114/ijsss.v7i1.3726
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Willingness to Care for Older Adults

Abstract: The older adult population has increased and is projected to grow. This population usually has chronic disorders that need continuous care. However, it has been reported nurses and nursing students have negative attitude towards older adults. This descriptive study aimed at investigating factors influencing nursing students' willingness to care for older adults. This study was conducted among 270 nursing students at the university in the United States from February 1 to February 28, 2017. Study participants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…However, several students in this study shared a dislike for caring for older adults in nursing home environments due to inaccurate views of gerontological nursing, and the belief that this care lacks stimulating cognitive challenges. Jang et al, (2019) found that nursing students' willingness to care for older adults was influenced by their experiences of volunteer work with older adults. Interestingly, first-year nursing students exhibited the highest willingness to care for older adults when compared to senior nursing students because of a shift in attitudes throughout the curriculum (Jang et al, 2019).…”
Section: How Could the Findings Be Used To Influence Policy Or Practi...mentioning
confidence: 99%
“…However, several students in this study shared a dislike for caring for older adults in nursing home environments due to inaccurate views of gerontological nursing, and the belief that this care lacks stimulating cognitive challenges. Jang et al, (2019) found that nursing students' willingness to care for older adults was influenced by their experiences of volunteer work with older adults. Interestingly, first-year nursing students exhibited the highest willingness to care for older adults when compared to senior nursing students because of a shift in attitudes throughout the curriculum (Jang et al, 2019).…”
Section: How Could the Findings Be Used To Influence Policy Or Practi...mentioning
confidence: 99%
“…The incorporation of more geriatric LTC (GLTC)‐related content in nursing curricula has been recognized as a pressing educational need. Many nursing students are not exposed to the specialized knowledge and skills needed to effectively serve older adults (Jang et al., 2019 ; Shen & Xiao, 2012 ). GLTC education is relatively new, and we have limited understanding of the perspectives students have of ageing populations (Chai et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 2015 ), Jang et al. ( 2019 ) and Jang, Oh, et al. ( 2019 ) revealed that anxiety about ageing negatively affects the expectancy and value aspects to choose geriatric nursing as a career and the willingness to care for older people.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, nursing students who had empathy for older people had a high willingness to care for them (Jang, Kim, et al., 2019 ; Jang, Oh, et al., 2019 ). Zhang et al.…”
Section: Resultsmentioning
confidence: 99%